Ecological Challenges and Injustice from a Missiological Perspective - Jung, Ji Young (Transformation, 2021)
Coupled with ecological challenges, injustice such as unfair resource distribution and exploitation over nature and the poor has been disproportionately inflicted upon the powerless. As we look at the nexus of ecological challenges and injustice, we find establishing social sustainability like redressing the issues of injustice is closely linked with attaining environmental sustainability. This paper attempts to look into the nexus of ecological challenges and injustice from a missiological perspective. In a missiological paradigm, a biblical concept of justice for the poor and the integrity of creation help us understand the relations of ecological challenges and injustice and offer insights into how to address these two interlinked issues. This article has academic significance of expanding the horizon of mission theology in linking missiology and environmental issues.